JENIS DAN KARAKTERISTIK KEKERASAN SEKSUAL PADA SISWA LAKI-LAKI DI SMA/SMK KOTA YOGYAKARTA - Abd Rahman; Siti Urbayatun (Universitas Tadulako, 2022)
This study aims to identify the types and characteristics of sexual violence in male students of SMA/SMK Yogyakarta City. This type of research is descriptive with a survey method. The sample size in the study was 380 men. Sampling was carried out at two schools, consisting of SMA Negeri 11 and SMK Private Bopkri 1 Yogyakarta. The sampling technique is by cluster random sampling. The measuring instrument used for the Child Sexual Abuse Questionnaire (CSAQ). Descriptive analysis using. The results showed that out of 172 respondents, the most experienced sexual violence with the item having been harassed by someone verbally or via the internet (whatsApp, Instagram, Facebook, email, telegram or other internet services and had been forced or urged to touch or kiss other people). on his lips, body and/or private parts) each of 76 (44.2%).The results of this study can be used as guidelines for school policy making in approaching students who experience sexual violence to take preventive measures so that it does not happen again and also psychotherapy that can be used to treat mental and emotional disorders of students who have experienced psychological trauma due to sexual violence they have experienced.